The Effect of Washing on the Quality Of Minced Catfish During Frozen Storage - JOSEPH, JOSE; PERIGREEN, P A (Fishery Technology, 2017)
The effect of washing minced catfish in water, sodium chloride solution (1%) and ascorbic acid solution (0.1 %) in improving the quality and frozen shelf-life has been studied. Washing improved the colour and reduced the non-protein nitrogen contents and extractable nitrogen. Denaturation was more in samples washed in salt and ascorbic acid solutions. Rancidity as measured by PV and organoleptic studies showed significant reduction in washed samples. The frozen storage life was significantly enhanced by washing.